2014
DOI: 10.1637/10680-100113-regr
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Avian PathogenicEscherichia colifrom Laying Hens in Belgium to Antibiotics and Disinfectants and Integron Prevalence

Abstract: Avian pathogenic Escherichia coli (APEC) causes huge annual losses in the poultry industry worldwide. Multiresistance against antibiotics of APEC strains is increasingly seen in broilers, although much is still unknown about strains from laying hens where use of antibiotics is limited. Disinfection can reduce the infection burden. However, little is known about the presence of resistance against these products. Ninety-seven APEC strains were isolated from Belgian laying hens. The resistance to different classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
6
23
0
Order By: Relevance
“…In the present study, the proportion of integron carriage among APEC isolates is consistent with previous studies worldwide [10, 27]. In a study conducted in Egypt on APEC isolated from septicemic broilers, higher prevalence was reported for class 1 and 2 (46.6 and 9.6%, respectively) [5].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the proportion of integron carriage among APEC isolates is consistent with previous studies worldwide [10, 27]. In a study conducted in Egypt on APEC isolated from septicemic broilers, higher prevalence was reported for class 1 and 2 (46.6 and 9.6%, respectively) [5].…”
Section: Discussionsupporting
confidence: 92%
“…The distribution of the MIC values for H2O2 showed a bimodal distribution with the majority of isolates showing MIC values of 32-64 µg mL -1 and 3 isolates showing a MIC value of 2 µg mL -1 (Figure 1 B).Considering previously published data(Oosterik et al, 2014), the isolates showing MIC values of 32-64 µg mL -1 are probably wild type strains, while the isolates showing a MIC value of 2 µg mL -1 are probably isolates with increased susceptibility. It was therefore concluded that there was no acquired resistance towards both glutaraldehyde and H2O2.…”
supporting
confidence: 79%
“…The ranges of MIC values of the retrieved isolates and quality control strains were similar to MIC ranges described earlier (Oosterik et al, 2014). Since no wild type cut-off values are yet available for disinfectants, acquired resistance was assumed when MIC values showed a bimodal, multimodal or tailing distribution.…”
Section: Disinfectant Micsmentioning
confidence: 82%
See 1 more Smart Citation
“…Resistance to ciprofloxacin in E. coli strains isolated from turkeys ranging from 22% to 61% were also demonstrated in a 2012 UK study by Gosling et al (30). In lying hens in Belgium, the level of resistance to nalidixic acid was 38% (31).…”
Section: Discussionmentioning
confidence: 77%